Prevalence and resistance characteristics of multidrug-resistant Streptococcus pneumoniae isolated from the respiratory tracts of hospitalized children in Shenzhen, China - Xing Shi; Sandip Patil; Qing Wang; Zihao Liu; Chunqin Zhu; Heping Wang; Yunshen Chen; Liqiang Li; Liang Yang; Yuejie Zheng; Shaowei Dong; Yanmin Bao (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundPCV13 introduction in China has led to a significant reduction of vaccine serotype Streptococcus pneumoniae. However, non-vaccine serotypes with highly resistance and invasiveness were often reported in the post-pneumococcal conjugate vaccine era and there was regional differences.MethodsA total of 669 S. pneumoniae strains were collected from the respiratory tracts of hospitalized children at Shenzhen Children’s Hospital in 2021 and 2022. Antimicrobial resistance (AMR) characteristics were assessed through antibiotic susceptibility testing performed with the VITEK 2 compact system. AMR genes and single nucleotide polymorphisms (SNPs) in pbp1a, pbp2b, and pbp2x were identified via analysis of whole genome sequencing data. Statistical examination of the data was conducted employing chi-square and Fisher’s exact tests.ResultsWe found that non-vaccine serotypes strains had accounted for 46.6% of all the pneumococcal isolated strains. The most common non-vaccine serotype is 23A, with a prevalence rate of 8.9%, followed by 15A (6.6%), 6E (5.7%), 34 (3.2%), and 15B (2.9%). The multidrug resistance rates (MDR) of vaccine serotypes were 19F (99.36%), 19A (100%), 23F (98.08%), 6B (100%), and 6C (100%). Meanwhile, the MDR of non-vaccine serotypes were 15B (100.00%), 6E (100%), 15C (100%), 34 (95.24%), and 23A (98.31%). Resistance rates of 6E to more than six antibiotic classes reached 89.47%, which is similar to 19F (83.33%) and 19A (90%). Unique resistance profiles were also identified for non-vaccine serotypes, including significantly higher resistance to chloramphenicol in 6E, 15B, and 15C than in 19F and 19A. Furthermore, through genome sequencing, we revealed strong correlation of cat-TC with chloramphenicol resistance, patA/patB with tetracycline resistance, ermB and pmrA with erythromycin resistance.ConclusionThe introduction of PCV13 into China from 2017 has led to a shift in the dominant composition of pneumococcal strains. There has been a notable rise and spread of multidrug-resistant non-vaccine serotypes among children. Specifically, the non-vaccine serotype 6E, which was not widely reported in China previously, has emerged. To comprehend the resistance mechanisms, it is crucial to further investigate the molecular and genetic characteristics of these non-vaccine serotypes.